The Effect of Culture – Based Approach in Improving Students’ Reading Comprehension on Spoof Text - Suherman, Rudi; Yusyfiana, Ana (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
This research was intended to investigate the effect of a culture-based approach in improving students’ reading comprehension on spoof text. For that purpose, a true experimental study was applied to the eleventh-grade students of SMAN 1 Soreang. The sample of this study was 88 students from that school. These students were divided equally into the control and experimental group. The experimental group was given the Culture-Based Approach (CBA) as the treatment in comprehending the text. The students’ scores of pre-test and post-test from both groups were statistically analyzed and compared by the T-test. The findings could be summarized that generally, students from the experimental group gained better achievement than from the control group on their post-test scores. The data analysis also showed that there was a significant difference between the mean score of the pre-test (53.45) and the post-test (58.39.). Furthermore, the result of the t-test (5.707) was relatively higher than the t- table (2.018) for a 0.5 percent level of significance. It indicated that the students’ achievement was significantly improved after the treatment of using a Culture-Based Approach. Thus, it is recommended that a Culture-Based Approach should be considered as an alternative choice for English teachers in teaching spoof text.